Introduction. (10th May 2018) - El-Mahdi, Rabab; Lust, Ellen
Abstract : The nation-state is in crisis. The increasing mobility of capital and information, unprecedented waves of people moving across borders, and rise of actors, such as ISIS, unwilling to abide by the rules of the Westphalian system, challenge the very notion of territoriality, citizenship, sovereignty, and the state's monopoly over the legitimate use of force. Studies on the Middle East and North Africa since the Arab uprisings took the region by storm, upending "conventional wisdom" held by many political scientists and scholars, have focused largely on the causes, genealogy, and procedural outcomes of the events. These are important, but as we shall see, the uprisings also highlighted the need to think carefully about how the modern state has changed, is being adapted, or has been superseded. How is the "state, " a foundational conceptual construct in the social sciences, to be located in light of these events? And to what extent do the concepts we employ and the language we use accurately reflect and allow us to interrogate realities, or do they obscure them? This roundtable aims to spark this much-needed discussion.